Exploiting internal pressurisation to enhance structural properties - Polenta, Valerio (2017)
The thesis investigates ways to use internal pressure in a favourable way. It focuses on the structural effects of internal pressurisation of mechanical components. The buckling phenomenon of shell structures is analysed in depth and the conducted work confirms the long known beneficial influence of the internal pressure on buckling and suggests how to exploit this to the utmost extent. Changes in failure modes, stiffness and dynamic response due to pressurisation are also considered.